ОСНОВНИТЕ ПРИНЦИПИ ЗА ВОДЕЊЕ НА ОПТИМАЛНА МОНЕТАРНА ПОЛИТИКА (Yearbook - Faculty of Economics, 2020)
The recent financial crisis, however, does require some major rethinkingabout the details of this basic framework for monetary policy strategy. Wenow recognize that the financial sector plays a very prominent role in themacro economy and makes it highly nonlinear at times ever, and in someways, moreso. The theory of optimal monetary policy starts by specifying anobjective function that represents economic welfare, that is, the well-being ofhouseholds in the economy, and then maximizes this objective function subjectto constraints that are provided by a model of the economy. Before the crisis,both the objective function and the model of the economy were based on theprinciples of the new neoclassical synthesis. The bad news is that we have justbeen through a once-in--hundred-year credit tsunami that has had a devastatingimpact on the economy that will last for years to come. The good news is thatmacro/monetary economists and central bankers do not have to go back to thedrawing board and throw out all that they have learned over the last forty years.Much of the science of monetary policy remains intact. However, the essenceof the optimal monetary policy and its stabilization policy is based on severalbasic principles that will be analised in more detail within this paper.
Keywords: Monetary Policy, principles, inflation, price stability, Nominal Anchor, The Time-Inconsistency Problem, Expectations.